2020
DOI: 10.2147/ppa.s252448
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors Influencing Medication Nonadherence to Pulmonary Tuberculosis Treatment in Tibet, China: A Qualitative Study from the Patient Perspective</p>

Abstract: Medication nonadherence is one of the most significant obstacles to tuberculosis (TB) control worldwide. Identification of the factors associated with medication nonadherence is important. However, few related studies have been carried out in Tibet. This study aimed to explore factors influencing medication nonadherence to pulmonary TB (PTB) treatment in Tibet, China, from the patient perspective. Patients and Methods: In this qualitative study, seventeen PTB patients in Tibet were recruited by purposive and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…As many people seek TTM as primary care, public health efforts should involve the TTM system to reduce diagnostic delay [ 21 ]. Others have reported similar patient experiences in the region and emphasized the need for links between TTM and western TB care [ 26 ]. Similar experiences of first seeking traditional healers or herbal remedies for TB symptoms have been reported globally including in Africa, South Asia and South America [ 34 – 38 ].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…As many people seek TTM as primary care, public health efforts should involve the TTM system to reduce diagnostic delay [ 21 ]. Others have reported similar patient experiences in the region and emphasized the need for links between TTM and western TB care [ 26 ]. Similar experiences of first seeking traditional healers or herbal remedies for TB symptoms have been reported globally including in Africa, South Asia and South America [ 34 – 38 ].…”
Section: Discussionmentioning
confidence: 88%
“…However, in practice, TB care in the region has proven difficult to operationalize for many reasons. Challenges impacting Xizang more broadly, and Xigaze specifically, include a shortage of skilled health workers to provide comprehensive ongoing care, inadequate diagnostic capacity and lab facilities, as well as harsh terrain and weather conditions, which disrupt patient and health workers’ travel thereby limiting ongoing care [ 25 , 26 ]. Despite NTP guidelines calling for DOTS and monthly follow-up, most patients receive self-administered therapy with limited health system contact, which has contributed to a high loss to follow-up across the continuum of TB care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 9 , 10 Besides, doctors, playing the dominant role in treatment process, will also directly influence the treatment effect of TB patients. 11 Patients’ trust in doctors is reflected in patients’ affirmation of doctors’ medical technology, prescription correctness and other treatment factors, and the more patients trust their doctors, the better their treatment effects will be. 12 Additionally, previous studies showed that satisfactory doctor–patient communication during medical services, including an explanation of drug use and illness status, psychological counseling, and so on, was also one of means to improve the treatment effects of patients.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 15 The determinants of treatment adherence are complex and the empirical relationship between medical staff and treatment adherence is still lacking. 11 , 16 Doctor–patient trust is one of the important issues in the doctor–patient relationship. 17 The higher the mutual trust, the more confident the patients will be about the treatment service offered by the doctors, and the more active he/she will be to participate in the treatment.…”
Section: Introductionmentioning
confidence: 99%